2019
DOI: 10.1155/2019/5065920
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Activity of Lycium barbarum Polysaccharide by Inhibiting Autophagy in Human Skin Squamous Cell Carcinoma Cells In Vitro and In Vivo

Abstract: Objective. This study is aimed at investigating the effects of Lycium barbarum polysaccharide (LBP) on the proliferation and apoptosis of human cutaneous squamous cell carcinoma A431 cells in vitro and in vivo via its regulation on autophagy. Methods. In vitro experiment: A431 cells were treated with different concentrations of LBP, and cell viability was measured by the CCK8 method. Flow cytometry was used to detect the cell apoptosis rate. The expression of Ki67, PCNA, cl-caspase-3, Bcl-2, and LC3II and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…As an ideal cell model, macrophages are commonly used to evaluate immune‐regulatory activity. As active substances, polysaccharides can stimulate macrophages to secrete nitric oxide (NO), TNF‐α, and IL expression, thereby improving the resistance of organisms to pathogenic microorganism invasion (Zeng et al., 2019). NO is a highly reactive‐free radical and considerable cytotoxic mediator, contributes to anticancer and antimicrobial activities of macrophages (Li et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…As an ideal cell model, macrophages are commonly used to evaluate immune‐regulatory activity. As active substances, polysaccharides can stimulate macrophages to secrete nitric oxide (NO), TNF‐α, and IL expression, thereby improving the resistance of organisms to pathogenic microorganism invasion (Zeng et al., 2019). NO is a highly reactive‐free radical and considerable cytotoxic mediator, contributes to anticancer and antimicrobial activities of macrophages (Li et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that LBP has a great potential in the treatment of various physiological and pathological processes. 51,52 LBP is composed of a complex mixture of polysaccharides and proteoglycans. Its main constituents include arabinose, glucose, galactose, mannose, rhamnose, xylose, and galacturonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that LBP has a great potential in the treatment of various physiological and pathological processes 51,52 . LBP is composed of a complex mixture of polysaccharides and proteoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…A polysaccharide-rich aqueous extract from Chinese wolfberry fruits reduced the proliferation of SW480 and Caco-2 cell lines, as observed by the crystal violet and MTT assays, with IC 50 values of 600 and 650 µg/mL respectively, after 4 days of incubation, with a high capacity to arrest cellcycle progression in the G0/G1 phase [191]. An ethanol extract from the dried fruit residue of this species was cytotoxic toward A431 cells, with an IC 50 value of 873.7 µg/mL after 24 h of incubation, determined by water-soluble tetrazolium-8-[2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2Htetrazolium] monosodium salt (CCK-8) assay [192]. The same authors conducted in vivo studies in mice submitted to an intraperitoneal injection of 50 mg/kg of the crude extract, reporting a lower volume and weight of the formed tumor and a higher survival rate of tumor-bearing nude mice [192].…”
Section: Solanaceae Familymentioning
confidence: 99%
“…An ethanol extract from the dried fruit residue of this species was cytotoxic toward A431 cells, with an IC 50 value of 873.7 µg/mL after 24 h of incubation, determined by water-soluble tetrazolium-8-[2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2Htetrazolium] monosodium salt (CCK-8) assay [192]. The same authors conducted in vivo studies in mice submitted to an intraperitoneal injection of 50 mg/kg of the crude extract, reporting a lower volume and weight of the formed tumor and a higher survival rate of tumor-bearing nude mice [192]. Several phenolic amides were isolated from an ethanol extract from the stem of L. barbarum and tested toward glioma cell lines, using the MTS method [180].…”
Section: Solanaceae Familymentioning
confidence: 99%